Valuation of health and nonhealth outcomes from next-generation sequencing: Approaches, challenges, and solutions - Regier, D; Weymann, D; Buchanan, J; Marshall, D; Wordsworth, S (Elsevier, 2018)
Background Next-generation sequencing (NGS) technologies have seen variable adoption in the clinic. This is partly due to a lack of clinical and economic studies, with the latter increasingly challenged to examine patient preferences for health and nonhealth outcomes (e.g., false-positive rate). Objectives To conduct a structured review of studies valuing patients’ preference-based utility for NGS outcomes, to highlight identified methodological challenges, and to consider how studies addressed identified challenges. Methods We searched MEDLINE (PubMed), Embase (Ovid), and Web of Science for published studies examining outcomes from health care decisions informed by NGS. We focused our search on direct elicitations of preference-based utility. We reviewed included studies and qualitatively grouped and summarized stated challenges and solutions by theme. Results Eleven studies were included. Most of them (n = 6) used discrete choice experiments to value utility. We categorized challenges into four themes: 1) valuing the full range of NGS outcomes, 2) accounting for accuracy and uncertainty surrounding effectiveness, 3) allowing for simultaneous multiple and cascading risks, and 4) incorporating downstream consequences. Studies found strong evidence of utility for NGS information, regardless of health improvement. Investigators addressed challenges by simplifying complex choices, by including health outcomes alongside nonhealth outcomes, and by using multiple elicitation techniques. Conclusions The breadth and complexity of NGS-derived information makes the technology a unique and challenging application for utility valuation. Failing to account for the utility or disutility of NGS-related nonhealth outcomes may lead to overinvestment or underinvestment in NGS, and so there is a need for research addressing unresolved challenges.